Epicrania fugax: an ultrabrief paroxysmal epicranial pain - Pareja, J A; Cuadrado, M L; Fernández-de-las-Peñas, C; Caminero, A B; Nieto, C; Sánchez, C; Sols, M; Porta-Etessam, J (Cephalalgia, 2008)
Ten patients (one man and nine women, mean age 48.8 +/- 20.1) presented with a stereotypical and undescribed type of head pain. They complained of strictly unilateral, shooting pain paroxysms starting in a focal area of the posterior parietal or temporal region and rapidly spreading forward to the ipsilateral eye (n = 7) or nose (n = 3) along a lineal or zigzag trajectory, the complete sequence lasting 1-10 s. Two patients had ipsilateral lacrimation, and one had rhinorrhoea at the end of the attacks. The attacks could be either spontaneous or triggered by touch on the stemming area (n = 2), which could otherwise remain tender or slightly painful between the paroxysms (n = 5). The frequency ranged from two attacks per month to countless attacks per day, and the temporal pattern was either remitting (n = 5) or chronic (n = 5). This clinical picture might be a variant of an established headache or represent a novel syndrome.